A Developmental Perspective on the Origins of Morality in Infancy and Early Childhood - Dahl, Audun; Killen, Melanie (Frontiers in Psychology, 2018)
Key constituents of morality emerge during the first four years of life. Recent research with infants and toddlers holds a promise to explain the origins of human morality. This article takes a constructivist approach to the acquisition of morality, and makes three main proposals. First, research on moral development needs an explicit definition of morality. Definitions are crucial for scholarly communication and for settling empirical questions. Second, researchers would benefit from eschewing the dichotomy between innate and learned explanations of morality. Based on work on developmental biology, we propose that developmental transitions involve coactions between genetic, environmental, and other processes. Third, attention is needed to discontinuities, alongside continuities, in the development of morality from infancy through childhood. Although infants and toddlers show behaviors that resemble the morally relevant behaviors of older children and adults, they lack an evaluative orientation, that is, they do not evaluate acts as morally right or wrong until later in childhood. We illustrate these points by discussing the development of two phenomena central to morality: Orientations toward helping others, and intergroup attitudes. We assert that a constructivist approach will help to bridge research on infants and toddlers with research on moral developmental later in childhood and into adulthood.